Analisis Penyebab Stres Pada Lansia Di Panti Sosial Tresna Werdha Budi Mulia 1 Cipayung Tahun 2023 - Stefanny Dian Pratiwi; Astrid Novita; Weslei Daeli (Vitamin : Jurnal ilmu Kesehatan Umum, 2024)
There is an increase in stress among the elderly at the Tresna Werdha Budi Mulia 1 Cipayung Social Home in 2023. It is suspected that this stress is caused by several trigger factors including missing family, feeling abandoned, not feeling free, fear of the disease they are suffering from, and fear of death. which can have an impact on poor health. Objective: To find out the causes of stress in the elderly at the Tresna Werdha Budi Mulia 1 Cipayung Social Home in 2023. Method: In this research, researchers used a qualitative approach with a case study type of research with descriptive methods. Results: The cause of stress in the elderly is due to psychosocial changes. This is because seniors often lose their personal belongings, seniors' relationships with other seniors are less harmonious, and room conditions are less conducive, which makes seniors unable to sleep. Stress due to psychosocial changes is also caused by elderly people who no longer have families, divorce from their partners, lose loved ones forever, feel abandoned and abandoned. Conclusion: From this research it can be concluded that the cause of stress in the elderly at the Tresna Werdha Budi Mulia 1 Cipayung Social Home is due to psychosocial changes. This is caused by several factors such as loss of valuables, less harmonious relationships with the elderly, less conducive room conditions, no longer existing family, loss of loved ones forever, and abandonment.